Penile Reconstruction of Congenital Urogenital Malformation: Penile Duplication, Bifid Scrotum, Symphisiolysis, and Remnant Urachus - Harsono, Anastasia Dessy; Budiman, Budiman; Sukasah, Chaula Luthfia (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: This report describes the penile reconstruction of a congenital urogenital malformation.Patient and Method: A 12 year-old boy came to our hospital with ‘penile duplication’, bifid scrotum, symphisiolysis, and remnant urachus. The procedures were done by the urologist, pediatric surgeon, and plastic surgeon. Urethral evaluation done by the urologist determined which penis was tenable, pediatric surgeon then excised the remnant urachus, and we performed urethroplasty onto the chosen urethra. The medial side of the penis was deepithelialized and both penis were put within one skin covering.Results: Patient was able to control micturition, and has normal erectile function. In the future, we plan to do further reconstruction of the pubic symphisiolysis at pubertal age.Summary: Surgery was performed by a team dedicated to their specialties. There is no single standard procedure for urogenital malformation, and we must emphasize the functional and aesthetic results in reconstruction surgery. It is important to master the basic principles of plastic surgery.